Memaknai Arti Kebebasan Manusia Pada Media Sosial Studi Kasus Pada Konten Youtube - Endang Pratiwi Kurniawan (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
As a social being, human freedom is something that cannot be measured. Every human being has freedom over himself, free to choose, act, and determine. Freedom in this social life of course has levels. Starting from the smallest environment, namely family, social, to the state. However, on the other hand, it can be said that there is no absolute absolute freedom. Basically every freedom has limitations. The meaning of this freedom actually cannot be separated from responsibility. It can be said that freedom and responsibility go hand in hand. This study aims to further analyze the freedom of expression, speech, and action seen from the scientific perspective of the philosophy of communication on the phenomena that occur in the digital era. In addition, this study wants to see whether the meaning of freedom on YouTube social media is still accompanied by the values of responsibility and norms in Indonesia.